Atlas of the forest sector in Slovakia - Ambrušová, Lucia; Halaj, Daniel; Ilavský, Ján; Marttila, Juhani (Finnish Forest Research Institute, 2013)
This atlas is a review of the current situation of the forest sector in Slovakia with a collection of maps. The cartographic information is grouped in the following way: forest resources, silviculture, wood harvesting, production and the most important producers of wood-based products, forest education and research and potential of wood energy. This review serves the information needs of different stakeholders and those interested in the forest sector in Slovakia.
Layout: Sari Elomaa/Metla
Keywords: Slovakia; bioenergia; metsäsektori; metsäteollisuus; bioenergy; forest industry; forest policy; forest resources; Slovakia; wood harvesting